THE RELATIONSHIP OF HEALTH PROMOTION STRATEGIES TO THE PREVENTION OF DIARRHEA DISEASE IN MADRASAH IBTIDAIYAH NEGERI 19 DARUL IMARAH DISTRICT, ACEH BESAR - Ananda, Iin Riska; Arbi, Anwar; Azwar, Eddy (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Aceh, 2023)
Background: Diarrhea is a public disease that still attacks babies, school children, teenagers, and even adults. Diarrhea attacks children more than adults. Based on data from UKS MIN (School Health Unit-Madrasah Ibtidaiyah Negeri) -19 Darul Imarah, cases of diarrhea among students in 2019 increased from month to month. Method: This research uses a cross- sectional approach. The research population was 42 teachers and employees at MIN-19 Darul Imarah. The research was carried out from March 19 to April 9, 2020. The research instrument was a questionnaire with data processing using Crosstab and Chi-Square test. This research aims to determine the relationship between advocacy, atmosphere building, and community empowerment movements in preventing diarrhea at MIN-19 Darul Imarah. Result: The research results showed that there was a relationship between advocacy health promotion strategies (p-value 0.005), the atmosphere-building health promotion strategies (p-value 0.032), and the community empowerment movement health promotion strategy (p-value 0.043) on prevention of diarrhea in Madrasah Ibtidaiyah Negeri 19 Darul Imarah District. Recommendation: It is hoped that the Principal of Madrasah Ibtidaiyah Negeri 19 Darul Imarah District will increase health promotion (advocacy, atmosphere building, and community empowerment movements) at school and outside of school in an effort to prevent diarrhea for students.